Employment Pattern of Migrant Labour in Punjab State: A Case Study - Jagjeet Singh Gill, Surabhi Sharma and Anil Sharma, (Indian Journal of Extension Education, 2017)
The study was undertaken with the objective to study the socio-economic profile of migrants, income, mode ofmigration and level of awareness of migrants for different schemes of central government. Three districts namedJalandhar, Mohali and Gurdaspur were selected. Gharuan and Bhago majra villages were selected from Kharar andMohali blocks of District Mohali. Shahpur and Khiala villages were selected from Jalandhar and Adampur blocks ofDistrict Jalandhar. Bhumbli and Kot yograj villages were selected from Dhariwal and Kahnuwan blocks of districtGurdaspur. List of permanent and casual labourers was prepared from each village. From such list, a sample of 25migrant labourers was prepared from each village. An interview schedule was prepared for collecting the responseof migrants keeping in view of the objectives of the study. Thus the total sample comprised of 150 migrants for thepresent study. The findings of the study revealed that more than 3/4th of the respondents were in the age group of0-30 years. The educational level of 79.33 per cent respondents was under matriculation. About 82.66 per cent of therespondents had family members of 5-8. More than half of the migrants were migrated from Bihar state. Out of 150migrants, 126 were male. More than ¾ of the respondents were completely aware of Pradhan Mantri Jan DhanYojana. Age and awareness about Pradhan Mantri Jan Dhan Yojana shows strong positive linear relationship.The mean monthly income of migrants came out to be Rs 7658, Rs 9177 and Rs 7729 in Gurdaspur, Mohali andJalandhar respectively